2021
DOI: 10.1186/s13046-021-01884-z
|View full text |Cite
|
Sign up to set email alerts
|

CPSF6 links alternative polyadenylation to metabolism adaption in hepatocellular carcinoma progression

Abstract: Background Alternative polyadenylation (APA) is an important mechanism of gene expression regulation through generation of RNA isoforms with distinct 3′ termini. Increasing evidence has revealed that APA is actively involved in development and disease, including hepatocellular carcinoma (HCC). However, how APA functions in tumor formation and progression remains elusive. In this study, we investigated the role of cleavage factor I (CFIm) subunit CPSF6 in human hepatocellular carcinoma (HCC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Previous studies have demonstrated that CPSF6 plays a pro-oncogenic role in several human cancers ( 13 , 18 , 19 ). Herein, we investigated the expression and functions of CPSF6 in ESCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that CPSF6 plays a pro-oncogenic role in several human cancers ( 13 , 18 , 19 ). Herein, we investigated the expression and functions of CPSF6 in ESCC.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, CPSF6 is highly expressed in aggressive breast cancer and is a clinically relevant marker of poor patient outcomes ( 12 ). In hepatocellular carcinoma, overexpression of CPSF6 increases cell proliferation, migration and invasion both in vitro and in vivo ( 13 ). Whereas, there are no studies concerning the biological roles of CPSF6 in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated their high expression levels in HCC cell lines, which were consistent in HCC samples through bioinformatics analyses. Several studies have shown that seven other miR-30 c target genes, including CPSF6 [ 37 ], KIAA1522 [ 38 ], XPO1 [ 39 ], SOX12 [ 40 ], PTBP3 [ 41 ], MYBL2 [ 42 ], and GALNT10 [ 43 ] had a pro-developmental effect on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The lentiviral vector pLKO.1-puro-shRNA- CPSF6 was constructed for CPSF6 knockdown as described previously ( Tan et al, 2021 ). The lentiviral vectors pCDH-PGK- VHL -CDS-short 3′UTR-SV40-NeoR and pCDH-PGK- VHL -CDS-long 3′UTR-SV40-NeoR were constructed for VHL overexpression.…”
Section: Methodsmentioning
confidence: 99%